2006
DOI: 10.1038/sj.ijo.0803206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between preclinical abnormalities of global and regional left ventricular function and insulin resistance in severe obesity: a Color Doppler Imaging Study

Abstract: Background: The aim of this study was to evaluate the relationship between insulin resistance and preclinical abnormalities of the left ventricular structure and function detected in severe obesity by Color Doppler Myocardial Imaging (CDMI). Forty-eight consecutive severely obese patients (Group O) (11 males, 37 females, mean age 32.877 years) were enrolled. Forty-eight sexand age-matched non-obese healthy subjects were also recruited as controls (Group C). All subjects underwent conventional 2D-Color Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
(28 reference statements)
9
41
1
Order By: Relevance
“…These strain imaging parameters appear to be related to the severity of obesity and can contribute to increased BMI. Furthermore, our results are similar to the previous study of results (6,7,30 Di Bello et al (30) evaluate the regional myocardial function in obese adult patients (n=48; mean age, 32.8 years) and showed that systolic strain and SR values were lower in the obese group than the controls, both at the septum and lateral wall level. It was reported by Lorch et al (2) that decreased diastolic dysfunction in obese children have recorded using the strain parameters (early diastolic SR and SR E/A ratios ) in the LV septal and lateral walls.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These strain imaging parameters appear to be related to the severity of obesity and can contribute to increased BMI. Furthermore, our results are similar to the previous study of results (6,7,30 Di Bello et al (30) evaluate the regional myocardial function in obese adult patients (n=48; mean age, 32.8 years) and showed that systolic strain and SR values were lower in the obese group than the controls, both at the septum and lateral wall level. It was reported by Lorch et al (2) that decreased diastolic dysfunction in obese children have recorded using the strain parameters (early diastolic SR and SR E/A ratios ) in the LV septal and lateral walls.…”
Section: Discussionsupporting
confidence: 82%
“…The STE-derived strain parameter is a relatively new parameter that is used to assess systolic and diastolic myocardial function (11,13,30). Obese subjects also had higher risk of a pseudonormalized diastolic pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few clinical studies of global LV function have taken into account either myocardial afterload or preload 74,76 (Table 1). The strain studies thus far published have used Doppler, 73,81,86 myocardial systolic and diastolic velocities, 67 or both 82 ( Figure 6), and velocity vector imaging to investigate LV twist and rotation. These studies consistently demonstrate lower levels of strain, velocities, strain rates, and torsion in obese patients with normal EF, compared with the control subjects.…”
Section: Systolic Functionmentioning
confidence: 99%
“…The public health ramifications are considerable, as obesity is an established risk factor for the development of heart failure, with effects on cardiovascular morbidity and mortality rates independent of commonly associated co-morbidities, such as coronary artery disease, hypertension and diabetes mellitus [3]. Subclinical left ventricular dysfunction is a common finding in overweight patients [4,5] and may progress over time to overt heart disease. As weight excess and insulin resistance are considered to mediate the link between obesity and cardiac function [5,6], successful strategies for weight reduction and improvement in metabolic status could improve left ventricular performance.…”
Section: Introductionmentioning
confidence: 99%